2009
DOI: 10.1016/j.molcel.2009.01.030
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Docking Surface on Calcineurin Mediates Interaction with Substrates and Immunosuppressants

Abstract: SUMMARY The phosphatase calcineurin, target of the immunosuppressants cyclosporin A and FK506, dephosphorylates NFAT transcription factors to promote immune activation and development of the vascular and nervous systems. NFAT interacts with calcineurin through distinct binding motifs: the PxIXIT and LxVP sites. While many calcineurin substrates contain PxIxIT motifs, the generality of LxVP-mediated interactions is unclear. We define critical residues in the LxVP motif, and demonstrate its binding to a hydropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
134
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(148 citation statements)
references
References 43 publications
10
134
2
1
Order By: Relevance
“…Notably, Tyr418 in CN V418Y/F419L , which is immediately N-terminal to the LxVP motif, fits into a deep pocket formed by the loops connecting EF hands 1 and 2 and EF hands 3 and 4 of CNB. This is consistent with the experimental observations that many LxVP motifs are immediately preceded by an aromatic residue (Phe or Tyr) [23], which may act as a binding strength enhancer.…”
Section: The Cna-cnb Interface Is a General Recognition Site For Aissupporting
confidence: 92%
See 1 more Smart Citation
“…Notably, Tyr418 in CN V418Y/F419L , which is immediately N-terminal to the LxVP motif, fits into a deep pocket formed by the loops connecting EF hands 1 and 2 and EF hands 3 and 4 of CNB. This is consistent with the experimental observations that many LxVP motifs are immediately preceded by an aromatic residue (Phe or Tyr) [23], which may act as a binding strength enhancer.…”
Section: The Cna-cnb Interface Is a General Recognition Site For Aissupporting
confidence: 92%
“…The substrates and regulators of CN contain at least one of the two conserved CN-binding motifs, PxIxIT and LxVP, which interact with two distinct docking sites on CN [3,[20][21][22][23]. Recently, Grigoriu et al [24] reported the first high-resolution structure of CN α bound to a physiological binding partner, the protein inhibitor A238L from African swine fever virus.…”
Section: The Cna-cnb Interface Is a General Recognition Site For Aismentioning
confidence: 99%
“…For example, nuclear accumulation of NFAT family of transcription factors in vertebrates and the stress-responsive transcription factor Crz1p in yeast is regulated by dephosphorylation mediated by the calcium/calmodulin-dependent calcineurin phosphatase (21)(22)(23)(24)(25)(26)(27)(28). Indeed, examination of the amino acid sequence of eIF6 shows that, in addition to a conserved docking motif for CK1 (FXXXF, where X is any amino acid) (29) at amino acid positions 34 -38, and well-characterized CK1 phosphorylation sites at Ser-174 and Ser-175, the protein also possesses a binding motif LXVP for the Ca 2ϩ -regulated protein phosphatase calcineurin (30). This putative calcineurin binding motif FIGURE 2.…”
Section: Intracellular Localization Of Eif6 In Mammalian Cells-tomentioning
confidence: 99%
“…In addition to the PXIXIT binding motif, a second calcineurin binding motif with a moderately conserved consensus sequence, LXVP lies near the C terminus of the NFAT regulatory region (33). Calcineurin binds to this site at a hydrophobic pocket formed at the interface of its two subunits A and B (30). This hydrophobic pocket formed at the interface of the two calcineurin subunits is targeted by the immunosuppressant-immunophilin complexes (e.g.…”
Section: Intracellular Localization Of Eif6 In Mammalian Cells-tomentioning
confidence: 99%
See 1 more Smart Citation